Hieronim ze Strydonu wobec homeizmu i problemów z własną biblioteką za pontyfikatu Damazego = Hieronimus from Stridon in the face of homeism and problems with his own library during the pontificate of Damasus - Spychała, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Hieronimus was one of the most prominent Christian writers in the fourth to fifth centuries after Christ. His work fell during the period of religious disputes known as the disputes over the doctrine of Arius. In fact, the basic dispute was between the supporters of co-eternity and the supporters of similarity. Hieronimus supported Pope Damasus in his struggle to implement the laws from Council of Nicea. In this struggle he used the resources of his own library, which he maintained, including, in the desert.
Keywords: Hieronim ze Strydonu (331 albo 347 - 419 albo 420); Ariusz (250-336); homeizm; Damazy I (papież; 305-384); Nicea; pustynia; Hieronimus; Arius; homoios; Damasus; desert